1996
DOI: 10.1007/bf01997786
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of anticonvulsant metabolites of progesterone in women with partial epilepsy in the intercritical phase

Abstract: The 3alpha-hydroxy metabolites of progesterone (P), 3alpha-hydroxy-5alpha-pregnan-20-one (allopregnanolone, A-PREG) and 3alpha-hydroxy-5beta-pregnan-20-one (pregnanolone, PREG), have been found to be among the most potent ligands of gamma-aminobutyric (GABA)-A receptors; in experimental animals, they have been found to have anxiolytic, hypnotic and anticonvulsant effects. Similar to those of the benzodiazepines and barbiturates that interact with GABA-A receptors. The present study was undertaken to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several investigations have shown a relationship between reproductive steroids and central nervous system excitability. The active metabolite of progesterone, allopregnanolone, is a neurosteroid which exhibits hypnotic, anxiolytic and anticonvulsant actions (Bitran et al 1991(Bitran et al & 1995Galli et al 1996;Korneyev & Costa 1996;Wilson & Biscardi 1997). Allopregnanolone exhibits potent inhibitory actions in the central nervous system, acting on the GABA-benzodiazepine-chloride channel macromolecular complex by an allosteric interaction with the GABA A receptor, with potentiation of the chloride channel current (Schumacher & Baulieu 1995;Rupprecht et al 1996;Brot et al 1997;Kellog et al 1998).…”
mentioning
confidence: 99%
“…Several investigations have shown a relationship between reproductive steroids and central nervous system excitability. The active metabolite of progesterone, allopregnanolone, is a neurosteroid which exhibits hypnotic, anxiolytic and anticonvulsant actions (Bitran et al 1991(Bitran et al & 1995Galli et al 1996;Korneyev & Costa 1996;Wilson & Biscardi 1997). Allopregnanolone exhibits potent inhibitory actions in the central nervous system, acting on the GABA-benzodiazepine-chloride channel macromolecular complex by an allosteric interaction with the GABA A receptor, with potentiation of the chloride channel current (Schumacher & Baulieu 1995;Rupprecht et al 1996;Brot et al 1997;Kellog et al 1998).…”
mentioning
confidence: 99%
“…It has been shown that allopregnanolone acts as a ligand to the GRC and increases Cl − current induced by GABA, decreasing brain excitability. In a previous experience, serum allopregnanolone levels were measured in 15 women with partial epilepsy in the intercritical phase, and no significant differences were found between patients and control subjects (18). The naturally occurring allopregnanolone is more potent than progesterone itself (16), and recent data suggest that hypnotic effects of progesterone are mediated through this metabolite (17).…”
mentioning
confidence: 90%
“…The naturally occurring allopregnanolone is more potent than progesterone itself (16), and recent data suggest that hypnotic effects of progesterone are mediated through this metabolite (17). In a previous experience, serum allopregnanolone levels were measured in 15 women with partial epilepsy in the intercritical phase, and no significant differences were found between patients and control subjects (18).…”
mentioning
confidence: 93%